2012
DOI: 10.1002/eat.20987
|View full text |Cite
|
Sign up to set email alerts
|

Severe anorexia nervosa in men: Comparison with severe AN in women and analysis of mortality

Abstract: Male inpatients should receive close follow-up after their discharge, especially if they have a restrictive form of AN, present low BMI, or are older at admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
5
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 39 publications
12
71
5
3
Order By: Relevance
“…Collectively, these reports converge with prior research suggesting premorbid obesity is more common among males than females [42]. One prior study, for example, found that 39% of male versus 13% of females admitted for inpatient treatment of AN between 1988 and 2004 were found to a history of overweight (BMI > 25) [35]. A Finnish twin study of lifetime AN found that higher BMI predated AN for the five probands, suggesting that "early overweight in otherwise vulnerable males seemed to have had a crucial role in triggering the dieting, which in turn (may) have led to AN" [57].…”
Section: Case Reports: An Illustration Of Clinical Presentationssupporting
confidence: 73%
See 1 more Smart Citation
“…Collectively, these reports converge with prior research suggesting premorbid obesity is more common among males than females [42]. One prior study, for example, found that 39% of male versus 13% of females admitted for inpatient treatment of AN between 1988 and 2004 were found to a history of overweight (BMI > 25) [35]. A Finnish twin study of lifetime AN found that higher BMI predated AN for the five probands, suggesting that "early overweight in otherwise vulnerable males seemed to have had a crucial role in triggering the dieting, which in turn (may) have led to AN" [57].…”
Section: Case Reports: An Illustration Of Clinical Presentationssupporting
confidence: 73%
“…An investigation of 1009 AN patients including 23 males hospitalized between 1988 and 2004 reported a SMR of 8.08 (1.62-23.62) for male patients and 10.6 (7.6-14.4) for female patients [35]. Long-term survival did not differ between genders; however, 3-year survival data suggested male patients died one year earlier than females (p = 0.017) following discharge from hospitalization.…”
Section: Mortality Risk Associated With Ed In Malesmentioning
confidence: 99%
“…In the general population, some recent epidemiological data suggest that as much as 25% of people with AN are male [8]. As the recent retrospective cohort study suggests, there may in fact be a higher short term (less than 3 year) post treatment mortality in males compared to females [10]. So it is a very important question that we should pay more attention to the male AN.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no previous article in English has demonstrated higher shortterm mortality in male EN patients. One study found that 3-year survival was significantly lower in male EN patients [20]. Those authors hypothesized that males received less social support after discharge.…”
Section: Discussionmentioning
confidence: 99%